Wrap-Attack Pack: Product Packaging Exercise. Issue 1 (2nd January 2016) - Lee, Seung Hwan (Mark); Hoffman, K. Douglas
Abstract : Although many marketing courses discuss traditional concepts pertaining to product strategy, concepts specifically relating to packaging are often glossed over. This exercise, "Wrap-Attack Pack, " teaches students about the utilitarian and hedonic design elements of packaging. More specifically, the primary objective is to creatively design a take-out box focusing on graphical and structural components, and provide theoretical justifications for design choices. Students reported that the exercise increased their creative input, helped them to acquire marketing skills, enhanced their learning experience, and increased course satisfaction. Alternative methods for conducting the exercise in online and/or resource-constrained instructional environments are also presented.